Internal Reflection Horizons (IRHs) in western Dronning Maud Land, East Antarctica from airborne radar surveys (4.8 - 91.0 ka) - Steven Franke; Daniel Steinhage; Veit Helm; Alexandra Zuhr; Olaf Eisen (PANGAEA, 2025)
We present internal reflection horizons (IRHs) from airborne radar data in western Dronning Maud Land, East Antarctica. The IRHs were dated at the EDML ice core and IRH ages range between 4.8 and 91.0 ka before present. Radar data were collected with the AWI EMR and UWB radar systems in period between summer seasons 1996/97 and 2023/24.